Wooden, wounded, defaced : performing the body in Irish theatre 1983-1993 - Sweeney, Bernadette (Trinity College (Dublin, Ireland). Department of Drama, 2002)
Wooden. Wounded. Defaced-Performing the Body in Irish Theatre 1983-1993 uses a four-chapter structure to consider the issues of performance and representation in Irish theatre, the specific circumstances within which Irish theatre is performed and the theoretical possibilities for an Irish performance theory. I have chosen three plays produced between 1983 and 1993, each significant in terms of the performance idiom and the placing of body, incorporating issues of representation, transformation and the recovery of tradition. In each case I focus on the liveness of the bodies of the actors and on the performance moment. Chapter 1 PERFORMING TRADITION explores cultural specificity to ask ‘Is there an Irish body?’ Irish performance traditions are investigated to find how the body has been sited within a broadly acknowledged literary tradition of theatre. In the third section of this chapter, ‘Literally Theatrical’, I consider marginalized stagings of the body in twentieth century Irish theatre that have set precedents for the three core plays of this thesis.
Keywords: Drama, Ph.D.; Ph.D. Trinity College Dublin